Structural Determinants of Student Lateness to School on Reopening Days: Evidence from Adidome Senior High School, Ghana (British Journal of Multidisciplinary and Advanced Studies, 2025)
++++++++++++++Timely student return on school reopening days is crucial for effective curriculum delivery and school management. This study investigates restraining factors influencing lateness among students in forms two and three at Adidome Senior High School, Ghana. A cross-sectional survey of 290 students measured lateness prevalence and assessed biographical, parental, student-related, and school-related factors. Lateness is a widespread structural challenge, with 74.5% of students reporting late (after Day 3). Logistic regression showed parental constraints significantly increased lateness (OR = 1.70, p = 0.006) while enhanced school communication policies and early academic engagement reduced it (OR = 0.47, p < 0.001). Student attitudes and demographic characteristics were not significant predictors. The findings highlight that effective interventions should prioritize parental financial support and improved institutional communication over punitive student measures. Recommendations include strengthening financial assistance schemes, refining communication protocols, and fostering community-school partnerships to advance educational punctuality in semi-rural settings.